Remoção do pesticida metomil de água e efluentes via fotólise e processos de oxidação avançada. - Lima, Jefferson Thiago da Silva (2017)
Most of humanity's creations and responses always surround a problematic. With each passing day it is more common for a problem to come up and, simultaneously, a solution. Regarding wastewater treatment, which always requires attention due to its increasing complexity, new methodologies, such as Advanced Oxidative Processes, have been studied and improved to meet the needs in an innovative way. The Advanced Oxidative Processes consist in the use of the hydroxyl radical to oxidize the organic matter present in effluents. They are currently considered the most efficient means in the degradation of pollutants present in wastewater and have been stood out, besides the efficiency in its purpose, for both technical and economical viability to be implemented. The aim of this work was to study processes based on advanced oxidation in the treatment of effluents containing the pesticide Metomil. Different processes, such as photolysis, photochemical H2O2/UV and the one based on the Fenton reagent (Photo-Fenton) were used in order to degrade the organic matter present in the bed and, then, compared to verify the efficiency of each one. The process using the Fenton reagent had a better result, degrading 99.79% of the pesticide Metomil in 30 minutes, while photolysis and photochemical degradation H2O2/UV took 50 and 35 minutes, respectively, to degrade the same percentage of insecticide